Natura Fluens: Time and Nature in Avicenna’s The Physics of Healing - M.Kemal Isik (Filozofia, 2023)
This work concerns Avicenna's account of nature, mainly as it engages with Aristotle’s Physics. By discussing two accounts of nature, particularly their treatment of motion and rest, I wish to highlight Avicenna's addendum to Aristotle's account of nature. Integral to my argument shall be Avicenna's emphasis on the necessity of understanding components of nature in temporal terms. Incorporating his idea of the ‘flowing now’ into nature, Avicenna's physics, I suggest, constantly emphasizes the place of temporality operative in natural occurrences. In doing so, he does not simply incorporate time into his account of nature but sees temporality as the necessary ground of the natural. Constantly asserting the temporal nature of motion and rest, he affirms the happening and event-based character of nature and highlights the becoming operative in it. He presents an account of nature qua natura fluens, or ‘flowing nature.’